Dietary inflammatory index and disability among older adults in Guangzhou: a cross-sectional analysis - Liao, Junbin; Cai, Wenfeng; Lin, Danrong; Xiao, Yuanyun; Liu, Yanxi; Wang, Yahui; Zhong, Yuquan; Xiao, Fan; Fang, Heng; Yao, Yilu; Lin, Yunfeng; Su, Jiewen; et al. (Frontiers in Public Health, 2025)
ObjectiveThis study aims to evaluate factors linked to the degree of disability among older adults and explore the relationship between the dietary inflammatory index (DII) and the degree of disability among older adults in southern China.MethodsConducted in two districts of Guangzhou, China, this cross-sectional study included 262 older adults with mild-to-severe disabilities. Disability levels were assessed using the “Assessment Standard for Long-term Care Disability” from the Medical Insurance Bureau, including Activities of Daily Living (ADL), Cognitive Ability, and Sensory Perception and Communication Skills (SPCS). Dietary data were collected via Food Frequency Questionnaire (FFQ) and used to calculate the DII and intake of nutrients (e.g., Protein, Carbohydrate and Fat). A multivariable ordinal logistic regression model was employed to analyze the influence of various factors and the DII on the degree of disability among older adults. Restricted cubic spline and sensitivity analyses were used to assess the association between DII and the degree of disability of the older adult population.ResultsInactivity (never exercising, OR = 8.48, 95% CI = 2.30–31.31) and reduced activity (formerly exercising, OR = 4.85, 95% CI = 1.39–16.96), stroke (OR = 2.78, 95% CI = 1.61–4.80), and dementia (OR = 2.69, 95% CI = 1.26–5.78) were significantly associated with increased disability. After adjusting for confounding factors, a higher DII was linked to a greater degree of disability, with the highest DII quartile showing a notably higher risk (OR = 2.61, 95% CI = 1.21–5.61) compared to the lowest quartile.ConclusionLack of exercise, previous exercise, stroke, and dementia are correlated with increased disability among older adults. Additionally, a higher DII is associated with a more severe degree of disability.